2018
DOI: 10.1149/2.1131809jes
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Perovskite Hybrid Electrocatalysts for Oxygen Reduction Reaction in Alkaline Media

Abstract: Developing a low-cost, and highly-efficient catalysts for improving oxygen reduction reaction (ORR) is imperative to the energy storage and conversion device. Here, we synthesized Ag/La 0.6 Sr 0.4 CoO 3-δ (Ag/LSC) composites by decorating LSC with Ag using the electroless technique. As a result, the LSC was homogenously overlaid with Ag nanoparticles. The derived Ag/LSC composites possessed a relatively higher specific surface area than pure LSC and Ag. The Co-O-Ag bonds in the composites contribute substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…We consider that the surface electronic transfer in the Ag-SSC composite was optimized by adding Ag into the SSC perovskite oxide, thereby leading to an increased ORR activity. A similar effect of the electron transfer effect has also been previously reported in other systems (Liu and Mustain, 2013; Han et al, 2014; Wang et al, 2018).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We consider that the surface electronic transfer in the Ag-SSC composite was optimized by adding Ag into the SSC perovskite oxide, thereby leading to an increased ORR activity. A similar effect of the electron transfer effect has also been previously reported in other systems (Liu and Mustain, 2013; Han et al, 2014; Wang et al, 2018).…”
Section: Resultssupporting
confidence: 86%
“…The Ag particle was fully distributed into the SSC nanoparticles with sizes of 1~10 μm (Figure 2a). However, the Ag particle had an irregular shape (Figure 2a), and the distribution of Ag in the SSC particles was demonstrated to be uneven (Figure 2c), which will adversely affect the activity of the composite catalyst (Guo et al, 2010; Park et al, 2015; Wang et al, 2018). In addition, the content of Ag in Ag-SSC was calculated based on the X-ray energy dispersive spectroscopy (EDX) results and listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al. optimised the composition of the Ag/La 0.6 Sr 0.4 CoO 3‐δ composite catalysts and demonstrated that 50 wt% Ag is needed to have the best results . However, even 50 wt% Ag catalyst still has a more negative half‐wave potential for O 2 reduction than commercial Pt/C.…”
Section: Orr On Ag Catalysts Deposited On Composite Supportsmentioning
confidence: 99%
“…[97] Wang et al optimised the composition of the Ag/La 0.6 Sr 0.4 CoO 3-d composite catalysts and demonstrated that 50 wt% Ag is needed to have the best results. [98] However, even 50 wt% Ag catalyst still has a more negative half-wave potential for O 2 reduction than commercial Pt/C. Gong et al achieved the ORR efficiency comparable to that of commercial Pt/C catalyst with Ag-WC/C catalyst in a microbial fuel cell as a result of synergistic effect between Ag and WC.…”
Section: Orr On Ag Catalysts Deposited On Composite Supportsmentioning
confidence: 99%
“…Combination of the active metal or metal oxides with perovskite oxides has been regarded as an available approach to improve ORR and OER activity. For instance, Zhou et al prepared Ag/La 0.6 Sr 0.4 CoO 3‐δ composites via decorating LSC with Ag 121 . The composite showed a comparatively larger specific surface area than both simple LSC and Ag because LSC overlaid homogenously Ag nanoparticles.…”
Section: The Design Strategies Of Perovskite‐based Oxides For Zabsmentioning
confidence: 99%